1998
DOI: 10.1177/0743554898134003
|View full text |Cite
|
Sign up to set email alerts
|

Doing Good Deeds

Abstract: In this study, adolescents' prosocial behavior toward parents was explored as an embedded aspect of parent-adolescent relationships. Gender, grade, attachment, and interdependency were examined as characteristics contributing to variation in adolescent prosocial behavior Adolescents (n = 129) in the 6th, 8th, and 10th grades; their mothers (n = 126); and their fathers (n = 104) completed questionnaires during two l-hour, in-home visits that were 1 week apart. For this study, the Adolescent Prosocial Behavior I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…We built on previous findings in which filial self-efficacy was related to adaptive functioning (e.g., Caprara, Pastorelli, et al, 2005); adolescents' sense of efficacy in dealing with local politics (i.e., an indicator of civic involvement) was related with their experiences in handling conflict between their parents ( Serek, Lacinov a, & Macek, 2012); and relational parentechild support was related with prosocial behaviors (Deater-Deckard et al, 2001;Eberly & Montemayor, 1998;Flanagan & Tucker, 1999;Laible & Carlo, 2004). We thus hypothesized that high levels of filial self-efficacy and relational parentechild support at age 16e17 would predict membership in stable high and/or increasing trajectories of prosocial behaviors from age 16e17 to age 22e23.…”
Section: The Current Studymentioning
confidence: 98%
“…We built on previous findings in which filial self-efficacy was related to adaptive functioning (e.g., Caprara, Pastorelli, et al, 2005); adolescents' sense of efficacy in dealing with local politics (i.e., an indicator of civic involvement) was related with their experiences in handling conflict between their parents ( Serek, Lacinov a, & Macek, 2012); and relational parentechild support was related with prosocial behaviors (Deater-Deckard et al, 2001;Eberly & Montemayor, 1998;Flanagan & Tucker, 1999;Laible & Carlo, 2004). We thus hypothesized that high levels of filial self-efficacy and relational parentechild support at age 16e17 would predict membership in stable high and/or increasing trajectories of prosocial behaviors from age 16e17 to age 22e23.…”
Section: The Current Studymentioning
confidence: 98%
“…One study yielded evidence of heterogeneity in trajectories as a function of target with most trajectories of prosocial behavior toward friends increasing from early to mid-adolescence, whereas prosocial behavior toward family members was stable or decreased slightly (Padilla-Walker, Carlo, & Nielson, 2015). Another study found that prosocial behavior toward family members increased from early to middle adolescence and then decreased from middle to late adolescence (Eberly & Montemayor, 1998). It is of note that research is less clear when it comes to changes in prosocial behavior toward strangers across adolescence, in part because individuals engage in such varying types of prosocial behavior toward strangers (Matsuba, Hart, & Atkins, 2007) and because we are not aware of any studies that have explored long-term age-related changes in adolescence using measures of prosocial behavior toward strangers.…”
Section: Longitudinal Change In Prosocial Behavior Toward Different Tmentioning
confidence: 99%
“…First, we examined growth in prosocial behavior toward strangers, friends, and family members to explore age-related changes in prosocial behavior from early adolescence through the early years of the transition to adulthood. Given the mixed findings in existing research (Carlo et al, 2007;Eberly & Montemayor, 1998;Padilla-Walker, Carlo, et al, 2015), in part due to variability in the target of prosocial behavior, it was difficult to make specific hypotheses, especially with regard to prosocial behavior toward strangers. However, based on existing research, we expected prosocial behavior toward friends to increase across adolescence and prosocial behavior toward family members to either remain stable or decrease slightly.…”
Section: The Current Studymentioning
confidence: 99%
“…Perhaps the most frequently studied link is the relation between parenting styles and prosocial behaviors. For example, several studies yield evidence that parental warmth and connectedness toward their child are related positively with prosocial behaviors (Eberly & Montemayor, 1998, 1999; Laible, Eye, & Carlo, 2008). Other investigations show that the authoritative parenting style (i.e., high levels of connectedness and moderate levels of control) is associated positively to prosocial behaviors (Baumrind, 1991; Dekovic & Janssens, 1992).…”
mentioning
confidence: 99%